Risk assessment after neoadjuvant chemotherapy in luminal breast cancer using a clinicomolecular predictor - Loibl, Sibylle; Weber, Karsten; Huober, Jens; Krappmann, Kristin; Marmé, Frederik; Schem, Christian; Engels, Knut; Pfitzner, Berit Maria; Kümmel, Sherko; Furlanetto, Jenny; Hartmann, Arndt; Darb-Esfahani, Silvia; et al. (Clinical cancer research, 2018)
Purpose: This study aimed to evaluate a modified EPclin test (mEPclin), a combination of EndoPredict (EP) score, post-neoadjuvant pathologic tumor size and nodal status, for predicting the risk of distance recurrence after neoadjuvant chemotherapy (NACT) in patients with residual estrogen receptor (ER)-positive/HER2-negative breast cancer. We also compared the prognostic power of the mEPclin with that of the CPS-EG score. - Experimental Design: A total of 428 formalin-fixed, paraffin-embedded tumor samples from GeparTrio and GeparQuattro studies were evaluated for mRNA expression of eight cancer-related and three reference genes. The mEPclin score was computed using a modified algorithm and predefined cut-off values were used to classify each patient at low or high risk. Primary endpoint was disease-free survival (DFS). - Results: A higher continuous mEPclin score was significantly associated with increased risk of relapse [HR, 2.16; 95% confidence interval (CI), 1.86-2.51; P < 0.001] and death (HR, 2.28; 95% CI, 1.90-2.75; P < 0.001). Similarly, patients classified at high risk by dichotomous mEPclin showed significantly poorer DFS and overall survival compared with those at low risk. In contrast with CPS-EG, the mEPclin remained significantly prognostic for DFS in multivariate analysis (HR, 2.13; 95% CI, 1.73-2.63; P < 0.001). Combining CPS-EG and other clinicopathological variables with mEPclin yielded a significant improvement of the prognostic power for DFS versus without mEPclin (c-indices: 0.748 vs. 0.660; P < 0.001). - Conclusions: The mEPclin score independently predicted the risk of distance recurrence and provided additional prognostic information to the CPS-EG score to assess more accurately the prognosis after NACT in the luminal non-pCR patient population. Therefore, this approach can be used to select patients for additional post-neoadjuvant therapies. Clin Cancer Res; 24(14); 3358-65. ©2018 AACR.